Wavelet transform based compression of electric signal waveforms for smart grid applications - Karthika, S.; P.Rathika, Dr. (International Journal of Engineering and Technology, 2019)
With the advent of smart grid concept a massive wide variety of measurement devices and smart monitors are to be deployed in the distribution network to allow broad observability and real time monitoring of the behavior of power system. The volume of data generated by the smart monitors and measurement devices are a tough challenge for storage, computation and transmission through the power Â Â system. As a result, the complexity of the power system increases tremendously. In order to increase the robustness of the power system data compression techniques are evolved, that aims to improve the efficiency of the data transmission and to reduce the storage issues. In the current work, to reduce the issues of data transmission and volume of data in power system, an efficient wavelet transform based data compression is introduced. The compression technique is performed through signal decomposition, thresholding of wavelet transform coefficients and signal reconstruction. The proposed technique is applied for Electric signals with disturbances. Simulation results are compared with the conventional discrete cosine transform. It is observed that the proposed data compression technique yields high compression ratio and also this technique can efficiently reconstruct the original signal.Â
Keywords: Smart Grid; Data Compression; Power System; Wavelet Transform; Signal Decomposition.